Analgesic and myorelaxant use of selected manual therapy techniques in patients with stomatognathic system (SS) disorders - Gębska, Magdalena; Opalko, Krystyna; Żyżniewski, Kuba; Weber-Nowakowska, Katarzyna; Jurczyk, Anna; Żyżniewska-Banaszak, Ewelina (Akademia Wychowania Fizycznego w Poznaniu)
Modern physical therapy employs a wide range of methods, e.g. manual therapy, physical therapy, massage, physiotherapy, which are also successfully used in dental specialization. The main purpose of application of these methods is elimination of pain and increased muscle tone. The aim of the study was to examine the effectiveness of manual therapy in elimination of pain and increased muscle tone in patients with disorders of the stomatognathic system (SS). The study was conducted in a group of 26 women who reported SS pain and muscular rigidity in the face. Patients were diagnosed using various manual and instrumental techniques. Ten procedures of manual therapy of the masseter muscle were carried out. A VAS pain assessment was carried out after each treatment. After the treatment cycle was completed, electromyography was performed on patients’ masseter muscles, and the range of jaw abduction was assessed. Manual therapy was proven to be an effective method of pain and increased muscle tone treatment in patients with an impairment of the SS. After a series of 10 treatments total pain relief and a decrease in the muscle tone were achieved, leading to an increase in the range of mandible abduction in all 26 female patients under study
Keywords: manual therapy; physical therapy; stomatognathic system